Missing Web References — A Case Study of Five Scholarly Journals - Bhat, Mohammad Hanief (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2009)
The present study attempts to ascertain the proportion of missing web references of 5-10 year-old research papers of the five leading open access (OA) journals in library and information science. The results suggest that the number of web citations has increased from 41.60% of all citations in 1998 to 53.32% in 2002. But a substantial quantity of web citations (32.09%) was found to be missing. The percentage of missing web citations goes on increasing with each passing year – ten-year-old publications having the highest number of missing citations, i.e., 39.96% and five-year-old publications having the lowest number of missing citations (25.89%). 0.92% of citations had moved to a new URL address and 74.14% of missing citations resulted in an HTTP 404 (page not found) error.